SOLUTION-FOCUSED MODELS OF CLINICAL SUPERVISION PRINCIPALS TO OVERCOME LEARNING GAPS IN POST-PANDEMIC ELEMENTARY SCHOOLS - Setyowati, Safitri; Prasetyo, Iis; Lenggono, Budi; Sari, Yessy Yanita (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
The problem of learning gaps was found to be predominant among students in post pandemic school. This study aims to determine solution-focused model of clinical supervision in elementary schools can overcome learning gaps. This research used collaborative classroom action research carried out in cycles. This research was carried out at Khoiru Ummah Integrated Islamic Elementary School. The objects in this study were students and class teachers at Khoiru Ummah Integrated Islamic Elementary School, which focused on the grade fifth. Data were collected using clinical supervision observation sheets. The collected data is then analyzed. The results can be seen in reducing the percentage of learning gaps. Pre-cycle shows a learning gap percentage of 82%. Then after cycle I, the learning gap percentage decreased to 47%. In cycle II, the learning gap decreased to 8%. Implementation of the solution-focused model by sharing, understanding class needs, and supporting teachers in determining appropriate learning methods. The results of this research show that solution focused model clinical supervision can improve the quality of teacher learning in terms of overcoming learning gaps in the classroom.